2016
DOI: 10.5812/pedinfect.38867
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cronobacter sakazakii Strains Isolated from Powdered Milk Infant Formula by Phenotypic and Molecular Methods in Iran

Abstract: Background: Cronobacter is a genus within the family Enterobacteriaceae and was previously known as Enterobacter sakazakii. Cronobacter sakazakii is an opportunistic ubiquitous bacterium and is identified throughout the world as an emerging food-borne pathogen. This pathogen causes meningitis, necrotizing enterocolitis (NEC), and sepsis (septicemia) in patients hospitalized in neonatal intensive care units and has a high mortality and morbidity rate. Contamination of powdered infant milk formula occurs more ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(25 reference statements)
2
8
0
1
Order By: Relevance
“…As prescribed for the treatment, in our study, more than 90% of the Cronobacter isolates were also susceptibility to piperacillintazobactam, gentamicin, amikacin, imipenem, meropenem, tetracycline, trimethoprim/sulfamethoxazole, ciprofloxacin, and chloramphenicol. Susceptibility to these antimicrobials has been reported in many countries: Brazil [30], China [9], and Iran [56]. In the current study, the multidrug resistance to at least three or more antimicrobial agents was detected in the 12 (18.8%) of Cronobacter isolates.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…As prescribed for the treatment, in our study, more than 90% of the Cronobacter isolates were also susceptibility to piperacillintazobactam, gentamicin, amikacin, imipenem, meropenem, tetracycline, trimethoprim/sulfamethoxazole, ciprofloxacin, and chloramphenicol. Susceptibility to these antimicrobials has been reported in many countries: Brazil [30], China [9], and Iran [56]. In the current study, the multidrug resistance to at least three or more antimicrobial agents was detected in the 12 (18.8%) of Cronobacter isolates.…”
Section: Discussionsupporting
confidence: 47%
“…Previous reports revealed the occurrence of resistance to the antimicrobial agents in Cronobacter spp. isolated from different sources [31,32,56]. Increasing resistance of Cronobacter against a range of cephalosporins and penicillins due to the production of β-lactamases has been reported [11,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…High rates of antibiotic resistance may result from the uncontrolled or inappropriate use of antibiotics. This can cause antibiotic-resistant bacteria to spread easily between hospital wards, leading to protracted outbreaks with high mortality and morbidity rates (35). The epidemiological information and monitoring system are, therefore, necessary to control Salmonella and Shigella infections in public health sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results with other studies in Iran, our findings showed a decrease in contamination rate of PIFs. According to Mardaneh and Dallal study in 2017 on 125 samples of PIFs, the contamination rate was reported 7.2% (Mardaneh & Dallal, ). On the other hand, contamination of baby foods in our study showed a higher contamination rate than some other studies, such as Abdel‐Galil et al, who reported only one contaminated sample (1.6%) (Abdel‐Galil et al, ) and lower contamination rate than (Aigbekaen & Oshoma, ; Iversen & Forsythe, ) studies who reported 27.1% (Aigbekaen & Oshoma, ) and 24%, respectively (Iversen & Forsythe, ).…”
Section: Resultsmentioning
confidence: 99%
“…This bacterium has been identified in various food sources, although its relevance to powdered infant formula (PIF) and baby food are major sources of concern (Biering et al, 1989;Teramoto et al, 2010;Yan et al, 2012). Raw materials of different origin or heatsensitive materials that are added to the PIF heating, extrinsic contamination of opened cans and carrier humans can be potential sources of bacteria (Abdel-Galil, Abdel-Latif, Ammar, & Serry, 2015;Jaradat, Al Mousa, Elbetieha, Al Nabulsi, & Tall, 2014;Mardaneh & Dallal, 2017).…”
mentioning
confidence: 99%